Indonesia dan Responsibility To Protect Etnis Muslim Rohingnya Myanmar - Hendra Maujana Saragih (Institut Agama Islam Negeri (IAIN) Curup, 2017)
This paper aims to identify and describe the Rohingya Myanmar Muslim ethnic conflicts over the past five years which can thus be gained informative findings that can provide concrete solutions to the end of the conflict in Myanmar and to describe the Indonesian response in resolving this ethnic conflict. This research uses the Concept of Responsibility to Protect (R2P), the Concept of Human Rights Violation in which the Rohingnya Muslim minority group has experienced stages of discrimination and social, cultural, religious, political and economic injustice. This resulted in a backlash from them by strengthening the resistance and spirit of the struggle and also attracted international attention and some countries in Southeast Asia especially Indonesia. This study included to human rights abuses and humiliation emphasizes research questions: How Indonesia Responses in Resolving Rohingya Ethnic Conflicts in Myanmar 2012-2017. The Urgency of this research is to see how the crime of humanity in Southeast Asia especially in Myanmar occurs systemically and the state participates in it. On the other hand ASEAN does not seem to have a clear sense of responsibility towards the community. Here Then where the response and action of Indonesia seen and observed concretely